HCV genotype-3a T cell immunity: specificity, function and impact of therapy - Humphreys, IS; von Delft, A; Brown, A; Hibbert, L; Collier, J; Foster, G; Rahman, M; Christian, A; Klenerman, P; Barnes, E (BMJ Publishing Group, 2012)
Background Hepatitis C virus (HCV) genotype-3a infection is now the dominant strain in South Asia and the UK. Characteristic features include a favourable response to therapy; the reasons for this are unknown but may include distinct genotype-3a-specific T cell immunity. In contrast to genotype-1 infection, T cell immunity to this subtype is poorly defined.